Measuring everyday creativity: A Rasch model analysis of the Biographical Inventory of Creative Behaviors (BICB) scale. (March 2021) - Silvia, Paul J.; Rodriguez, Rebekah M.; Beaty, Roger E.; Frith, Emily; Kaufman, James C.; Loprinzi, Paul; Reiter-Palmon, Roni
Highlights: The psychometric properties of the BICB were evaluated using the Rasch model. With some exceptions, item fit and local independence were good. Item difficulty was moderate and varied over a broad range. Some items showed differential item functioning for gender and age. The BICB appears to be a good self-report tool for research on everyday creativity. Abstract: Research on everyday creativity—the "little c" creative activities people do in their everyday lives—commonly uses self-report scales to assess people's engagement in different activities. The present research presents a detailed psychometric analysis of the Biographical Inventory of Creative Behaviors (BICB), a 34-item yes/no checklist of common creative activities that has become one of the most popular self-report measures of everyday creative behaviors. Based on a sample of 2, 359 adults, the reliability, dimensionality, item fit, item difficulty, and test information were evaluated from a Rasch model perspective. Overall, the BICB shows good evidence for score reliability and appears essentially unidimensional; a small cluster of misfitting and locally dependent items were flagged for impairing unidimensionality. The items' difficulty level was generally moderate and suitable for the scale's intended populations and purposes. Differential item functioning (DIF) based on gender and age, estimated via Rasch tree recursive partitioning methods, found notable gender-based DIF (generally reflecting culturally gendered qualities of some creative activities) but little age-based DIF. Taken together, the BICB has many psychometric strengths. Some opportunities for future scale refinement are discussed.